Management Options for Contaminated Urban Soils to Reduce Public Exposure and Maintain Soil Health. Issue 2 (1st March 2017) - Obrycki, John F.; Basta, Nicholas T.; Culman, Steven W.
Abstract : Soil management in urban areas faces dual challenges of reducing public exposure to soil contaminants, such as lead (Pb) and polycyclic aromatic hydrocarbons, and maintaining soil function. This study evaluated three management options for an urban lot in Cleveland, OH, containing 185 to 5197 mg Pb kg −1 and 0.28 to 5.50 mg benzo(a)pyrene kg −1 . Treatment options included: (i) cap the site with a soil blend containing compost and beneficially reused dredged sediments, (ii) mix compost with the soil, and (iii) mix compost and sediments with the soil. The soil blend cap reduced surface soil Pb to 12.4 mg Pb kg −1 and benzo(a)pyrene content to 0.99 ± 0.41 mg kg −1 . Aggregate stability for 2‐ to 0.25‐mm aggregates in the soil blend cap was 13% compared with the 38% aggregate stability in the urban soil. Mixing compost with the soil reduced benzo(a)pyrene content, but sample variability indicated that elevated spots likely remained exposed at the surface. Compost addition diluted soil Pb and increased aggregate stability to 60%. Mixing compost and sediments with the soil was the only management option accomplishing both management goals of reducing surface soil contaminants and maintaining soil health. For this combined mixing option, aggregate stability was 37%, soil Pb was 15 mg kg −1, and benzo(a)pyrene was 0.99 ± 0.09 mg kg −1 . Food‐grade oil addition did not increase benzo(a)pyrene degradation. Future studies should evaluate how incorporating soil blends in different soil types with a range of contaminants may offer a suitable long‐term management option for urban soil contaminants. Core Ideas: Soil blend incorporation maximized soil health and human health benefits. Soil capping may cover contaminants but reduced surface soil aggregate stability short term. Compost addition maintained surface aggregate stability and diluted Pb surface contamination. Incorporating soil blends offers a potential long‐term urban soil management solution.